Comparing the effects of massed and distributed practice on skill acquisition for children with autism. Issue 2 (11th May 2015) - Haq, Shaji S.; Kodak, Tiffany; Kurtz‐Nelson, Evangeline; Porritt, Marilynn; Rush, Kristin; Cariveau, Tom
<x xml:space="preserve">Abstract</x> We replicated and extended the findings of Haq and Kodak (2015) by evaluating the efficiency of massed and distributed practice for teaching tacts and textual and intraverbal behavior to 3 children with autism. Massed practice included all practice opportunities conducted on 1 day during each week, and distributed practice included practice opportunities conducted across several days during the week. The results indicated that distributed practice was more efficient for all participants. Suggested areas for future research and implications for practice are discussed.